Pelatihan Konversi Sampah Organik Menjadi Pupuk Organik Cair (Poc) Pada Level Rumah Tangga - Hidayati, Fajrina; Lessmana , Oka; Rahim, Beni; Putra, Ashar Nuzulul; Rahmat, Andree Auiia (SEGANTANG LADA : JURNAL PENGABDIAN KESEHATAN, 2024)
The existing temporary waste disposal sites (TPS) are no longer sufficient to accommodate the increasing amount of waste. As a result, many residents dispose of their waste improperly. Along with the growing population, the volume of waste also increases. If waste is not managed properly, it can lead to significant issues, such as negative impacts on health and environmental cleanliness. In RT 11, Bagan Pete Village, Alam Barajo District, Jambi City, this issue is quite noticeable because there is no proper waste management system in place. Residents often dispose of household waste in random places, including along main roads. This community service activity aims to enhance the knowledge of RT 11 residents about the processing of organic waste into liquid organic fertilizer (POC). The service is carried out through outreach and training on making POC from household organic waste. The event was held at one of the residents' homes and attended by 25 housewives invited by the RT head. The outreach was conducted using a presentation media and distributing leaflets about household organic waste. Afterward, participants were given hands-on training on how to make POC. The outcome of this activity is an increased understanding among the community about organic waste and how to manage it. Residents were also trained to make POC, which can be used to fertilize plants in their yards. It is hoped that, through this outreach and training, the residents of RT 11 will be able to manage organic waste independently, reduce the habit of improperly disposing of waste, and create a cleaner and healthier environment.